Diet selection of African elephant over time shows changing optimization currency - Pretorius, Y.; Stigter, J. D.; de Boer, W. F.; van Wieren, S. E.; de Jong, C. B.; de Knegt, H. J.; Grant, C. C.; Heitkönig, I.; Knox, N.; Kohi, E.; Mwakiwa, E.; Peel, M. J. S.; et al. (Oikos, 2012)
Multiple factors determine diet selection of herbivores. However, in many diet studies selection of single nutrients is studied or optimization models are developed using only one currency. In this paper, we use linear programming to explain diet selection by African elephant based on plant availability and nutrient and deterrent content over time. Our results indicate that elephant at our study area maximized intake of phosphorus throughout the year, possibly in response to the deficiency of this nutrient in the region. After adjusting the model to incorporate the effects of this deficiency, elephant were found to maximize nitrogen intake during the wet season and energy during the dry season. We reason that the increased energy requirements during the dry season can be explained by seasonal changes in water availability and forage abundance. As forage abundance decrease into the dry season, elephant struggle to satisfy their large absolute food requirements. Adding to this restriction is the simultaneous decrease in plant and surface water availability, which force the elephant to seek out scarce surface water sources at high energy costs. During the wet season when food becomes more abundant and energy requirements are satisfied easier, elephant aim to maximize nitrogen intake for growth and reproduction. Our study contributes to the emerging theory on understanding foraging for multiple resources.